2018
DOI: 10.1002/ecy.2397
|View full text |Cite
|
Sign up to set email alerts
|

Good neighbors make good defenses: associational refuges reduce defense investment in African savanna plants

Abstract: Intraspecific variation in plant defense phenotype is common and has wide-ranging ecological consequences. Yet prevailing theories of plant defense allocation, which primarily account for interspecific differences in defense phenotype, often fail to predict intraspecific patterns. Furthermore, although individual variation in defense phenotype is often attributed to ecological interactions, few general mechanisms have been proposed to explain the ubiquity of variable defense phenotype within species. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 63 publications
3
31
1
Order By: Relevance
“…As a result, intraspecific neighbourhood effects varied unimodally with respect to aggregation of high‐nicotine plants, with a peak at intermediate density. Although a number of studies have discussed potential mechanisms of neighbourhood effects (mostly interspecific effects; Andow, ; Barbosa et al, ), a very few studies have reported the operation of multiple mechanisms that simultaneously work in a spatial context (but see Coverdale et al, ; Kim & Underwood, ). Kim and Underwood () stressed that frequency‐dependent neighbourhood effects could be nonlinear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, intraspecific neighbourhood effects varied unimodally with respect to aggregation of high‐nicotine plants, with a peak at intermediate density. Although a number of studies have discussed potential mechanisms of neighbourhood effects (mostly interspecific effects; Andow, ; Barbosa et al, ), a very few studies have reported the operation of multiple mechanisms that simultaneously work in a spatial context (but see Coverdale et al, ; Kim & Underwood, ). Kim and Underwood () stressed that frequency‐dependent neighbourhood effects could be nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…resource concentration; Root, 1973) and delay a patch-leaving decision (Stephens & Krebs, 1986;Waage, 1979). Thus, neighbourhood effects caused by the repellent effects of nicotine varied depending on aggregation of highly Andow, 1991;Barbosa et al, 2009), a very few studies have reported the operation of multiple mechanisms that simultaneously work in a spatial context (but see Coverdale et al, 2018;Kim & Underwood, 2015). Kim and Underwood (2015)…”
Section: Density-dependent Intraspecific Neighbourhood Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of investment in N‐free secondary metabolites by the second broad‐leaved species, G. tenax , was also surprising, but consistent with our finding that growth of this species is severely negatively affected by large browsers, and with previous work showing substantial declines in all size classes of G. tenax in the presence of browsers in this savanna (Augustine & McNaughton, ; Sankaran et al, ). Rather than employing any form of costly chemical defence, this species appears to coexist (uneasily) with browsers by increasing the complexity of its branching architecture (BI), and growing in close association with other thorny species that create structural refugia where G. tenax saplings are protected from browsers (personal observation by all authors, see also Coverdale, Goheen, Palmer, & Pringle, ). One value of this strategy is that when browsing pressure is removed or low, the lack of investment in costly defences, combined with high leaf N, allows for rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have considered only associational effects involved in interspecific interactions, such as plant species diversity (e.g., Andow, 1991). Similar arguments on associational effects would also apply to intraspecific interaction, that is, interactions among conspecific plants with different phenotypes and/or genotypes (Champagne et al, 2018;Coverdale, Goheen, Palmer, & Pringle, 2018). For example, within a population of Solidago altissima, genotypic diversity of co-occurring plants decreased herbivory on the focal plants (i.e., associational resistance), although the mechanism was unclear (Genung, Crutsinger, Bailey, Schweitzer, & Sanders, 2012).…”
mentioning
confidence: 99%